2023
DOI: 10.3389/fpsyg.2023.1073529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of academic self-regulation on procrastination, academic stress and anxiety, resilience and academic performance in a sample of Spanish secondary school students

Abstract: IntroductionOne of the biggest challenges facing students today is procrastination, which is closely related to stress, anxiety and, in the most severe cases, depression. The aim of the present study is to analyze the influence of academic self-regulation on procrastination, academic anxiety and stress, academic resilience and academic performance.MethodThe sample consisted of 991 high school students aged between 16 and 19 years (M = 17.25; SD = 3.45). A structural equation model was used to analyze the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, Steel (2007) identified procrastinators' personality traits as low self-motivation, mental disorganization, low self-control, and lack of progress motivation (Steel, 2007). Previous research has also identified self-motivation and self-regulation as the most significant predictors of academic procrastination (Hussein, 2021;Ragusa et al, 2023). Howell et al (2006) also view academic procrastination as a deficiency in self-regulation (Howell et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, Steel (2007) identified procrastinators' personality traits as low self-motivation, mental disorganization, low self-control, and lack of progress motivation (Steel, 2007). Previous research has also identified self-motivation and self-regulation as the most significant predictors of academic procrastination (Hussein, 2021;Ragusa et al, 2023). Howell et al (2006) also view academic procrastination as a deficiency in self-regulation (Howell et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…From this perspective, procrastination is a self-protection method or a coping mechanism. Academic procrastination is also one of the most common emotional-cognitive-behavioral problems, with a prevalence rate of about 30 to 50 percent during the academic period reported which can reduce the learning process in students (Nikbakht et al, 2014;Ragusa et al, 2023;Steel & Klingsieck, 2016;Xu, 2023;Yockey, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This will assist learners in identifying key factors and improving their performance. Many college students struggle with their academic performance due to various factors (Ragusa et al, 2023). This trend is also present in Pangasinan Merchant Marine Academy, which is the focus of this study.…”
Section: Introductionmentioning
confidence: 85%
“…The signi cant in uence of cognitive self-regulation on academic stress is remarkable. Research has shown a negative association between self-regulation and academic stress, indicating that increased self-regulation is associated with lower levels of academic stress [24] [25]. Therefore, students who possess highly developed self-regulation skills demonstrate greater stress management abilities in academic environments [26] [27].…”
Section: Introductionmentioning
confidence: 99%